Human-powered vehicle capable of movement in the longitudinal and lateral directions - Hiroki KATO; Masaharu KOMORI; Tatsuro TERAKAWA (Journal of Advanced Mechanical Design, Systems, and Manufacturing, 2020)
Human-powered vehicles, especially conventional wheelchairs, are essential tools for people with lower body disability. But their movement in a lateral direction is limited or impossible, which burdens users who want to change directions, especially in a narrow space. Thus, a human-powered vehicle that can move in a lateral direction is required. To move in any direction, many motor-driven omnidirectional vehicles have been proposed, but humans cannot manually power their mechanisms. To solve this problem, we are developing a human-powered vehicle, that is, driven by hands of the rider, that can move in both the longitudinal and lateral directions. This paper proposes such a vehicle, which has a mechanism to move in the lateral direction like people can do while walking. We designed it so that riders can operate its mechanism by analyzing the space reachable by the rider’s palms where they can effectively exert power. We constructed a prototype and conducted experiments to confirm that the vehicle moves as expected with relatively low effort. In the experiments, we confirmed the validity of vehicle operation by comparing the moving time of the vehicle with and without the lateral translation function for different travel distances and passage widths. Our results showed that the proposed vehicle moves more quickly or requires shorter moving distance in comparison with a conventional wheelchair because of the lateral movement function. In addition, we found that the threshold for utility of the function is whether the passage width is larger than the vehicle diagonal length.